The mite Machrocheles robustulus (Mesostigmata, Macrochelidae) a new promising natural enemy of Haemonchus contortus (Strongylida, Trichostrongylidae) - Adrien Bamière; Julie Petermann; Damien Morel; Philippe Jacquiet; Christelle Grisez (Parasites & Vectors)
Abstract Background Antiparasitic resistance in sheep necessitates non-chemical strategies for gastrointestinal strongylosis control. We have evaluated the potential of three predatory mite species—Macrocheles robustulus, Macrocheles muscaedomesticae and Rhabdocarpais consanguineus—to reduce transmission of the nematode Haemonchus contortus by preying on infective larvae. Methods Under laboratory conditions, mites were exposed to mixed prey environments containing housefly Musca domestica eggs and H. contortus third-stage (L3) larvae. Predation was first monitored over 8 h. This was followed by a more detailed assessment of M. robustulus predatory capacity in sheep feces containing eggs of H. contortus and then the oviposition capacity of females was studied when fed exclusively with L3 larvae. Results Macrocheles robustulus demonstrated a significant preference for nematode larvae, leading to further evaluation of its predatory capacity in sheep feces containing 2250 eggs per gram of H. contortus. After 14 days at 25 ± 2 °C, the presence of M. robustulus resulted in a significant reduction of L3 larvae compared to controls (519 vs. 1067 L3 larvae; p < 0.05). Additionally, M. robustulus females oviposited when fed exclusively on nematode larvae. Conclusions These findings suggest that M. robustulus could be a viable biological control agent against H. contortus in pasture settings, warranting further field studies. Graphical abstract